“Sea Peoples” Up-To-Date. New Research on Transformations in the Eastern Mediterranean in the 13th-11th Centuries BCE. Proceedings of the ESF-Workshop held at the Austrian Academy of Sciences, Vienna, 3-4 November 2014 - Fischer, Peter M. (2017)
= Österreichische Akademie der Wissenschaften. Denkschriften der Gesamtakademie LXXXI